Some characteristics of age parameter for Yakutsk array data - R Razavi; SJ Fatemi (Iranian Journal of Physics Research, 2011)
In this paper some characteristics of age parameter(s) are studied on the basis of showers from Yakutsk array data [1] having energy ranging from 1018 eV to 1019 eV.